STILT mole fraction time series from Svartberget (35.0 m) - Christoph Gerbig; Ute Karstens; Frank-Thomas Koch (Integrated Carbon Observation System, 2022)
Gerbig, C., Karstens, U., Koch, F. (2022). STILT mole fraction time series from Svartberget (35.0 m), 2018-01-01–2018-12-31, ICOS RI, https://hdl.handle.net/11676/IrJN203dFhuUW8eZFgB4kGck
Keywords: Carbon Portal; ICOS; STILT; time instant, UTC; time instant, UTC; model CO2 dry air mole fraction; model CO2 dry air mole fraction; model CO2 dry air mole fraction component; model CO2 dry air mole fraction component; wind direction; wind direction; wind speed; wind speed; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap